A post hoc study on gene panel analysis for the diagnosis of dystonia. Issue 4 (10th February 2017) - van Egmond, Martje E.; Lugtenberg, Coen H.A.; Brouwer, Oebele F.; Contarino, Maria Fiorella; Fung, Victor S.C.; Heiner‐Fokkema, M. Rebecca; van Hilten, Jacobus J.; van der Hout, Annemarie H.; Peall, Kathryn J.; Sinke, Richard J.; Roze, Emmanuel; Verschuuren‐Bemelmans, Corien C.; et al.
ABSTRACT: Background : Genetic disorders causing dystonia show great heterogeneity. Recent studies have suggested that next‐generation sequencing techniques such as gene panel analysis can be effective in diagnosing heterogeneous conditions. The objective of this study was to investigate whether dystonia patients with a suspected genetic cause could benefit from the use of gene panel analysis. Methods : In this post hoc study, we describe gene panel analysis results of 61 dystonia patients (mean age, 31 years; 72% young onset) in our tertiary referral center. The panel covered 94 dystonia‐associated genes. As comparison with a historic cohort was not possible because of the rapidly growing list of dystonia genes, we compared the diagnostic workup with and without gene panel analysis in the same patients. The workup without gene panel analysis (control group) included theoretical diagnostic strategies formulated by independent experts in the field, based on detailed case descriptions. The primary outcome measure was diagnostic yield; secondary measures were cost and duration of diagnostic workup. Results : Workup with gene panel analysis led to a confirmed molecular diagnosis in 14.8%, versus 7.4% in the control group ( P = 0.096). In the control group, on average 3 genes/case were requested. The mean costs were lower in the gene panel analysis group (€1822/case) than in the controls (€2660/case). The duration of the workup was considerably shorter with gene panel analysis (28 vs 102 days). Conclusions : Gene panel analysis facilitates molecular diagnosis in complex cases of dystonia, with a good diagnostic yield (14.8%), a quicker diagnostic workup, and lower costs, representing a major improvement for patients and their families. © 2016 International Parkinson and Movement Disorder Society